2003
DOI: 10.2214/ajr.181.5.1811335
|View full text |Cite
|
Sign up to set email alerts
|

Using Superparamagnetic Iron Oxide–Enhanced MRI to Differentiate Metastatic Hepatic Tumors and Nonsolid Benign Lesions

Abstract: When evaluating metastatic liver tumors on SPIO-enhanced MRI, we recommend that heavily T1- and T2-weighted gradient-echo images be obtained with our parameters to exclude hemangiomas or cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…No signiˆcant diŠerence was seen in the ADC measurements of the pancreas and right and left kidneys. Superparamagnetic iron oxide (SPIO) 6,[21][22][23][24][25][26][27][28][29] With the application of diŠusion gradients in liver imaging, signals from vascular structures and simple liver cysts can be reduced, allowing easier detection of liver lesions without the distraction of possible pseudo-lesions, such as those commonly observed on SPIO-enhanced T2 * -weighted images. Two problems are reported for non-SPIO-mediated DWI.…”
Section: Measuring Adcmentioning
confidence: 99%
“…No signiˆcant diŠerence was seen in the ADC measurements of the pancreas and right and left kidneys. Superparamagnetic iron oxide (SPIO) 6,[21][22][23][24][25][26][27][28][29] With the application of diŠusion gradients in liver imaging, signals from vascular structures and simple liver cysts can be reduced, allowing easier detection of liver lesions without the distraction of possible pseudo-lesions, such as those commonly observed on SPIO-enhanced T2 * -weighted images. Two problems are reported for non-SPIO-mediated DWI.…”
Section: Measuring Adcmentioning
confidence: 99%
“…It is our opinion that ferucarbotranenhanced dynamic MR imaging with T2-weighted echoplanar sequence is hardly used to differentiate cysts from other focal lesions. For that purpose, the charac- teristic signal-intensity pattern on T2-weighted and heavily T1-weighted images (12) or ring enhancement on heavily T1-weighted images (13) could be helpful. In contrast, with regard to hemangiomas, a characteristic enhancement pattern was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 Quantitative Assessment of Liver and Spleen SNR and Lesion-to-Liver CNR GRASE can be used in combination with other techniques. The use of SPIO administration can improve the detectability of malignant hepatic lesions on T2-weighted and T2*-weighted images (25,26). Some investigators reported that the T2*-weighted GRE technique was superior to T2-weighted SE, fast SE, and HASTE for the detection of malignant liver tumor after administration of SPIO (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The use of SPIO administration can improve the detectability of malignant hepatic lesions on T2-weighted and T2*-weighted images (25,26). Some investigators reported that the T2*-weighted GRE technique was superior to T2-weighted SE, fast SE, and HASTE for the detection of malignant liver tumor after administration of SPIO (25,26). The higher susceptibility contrast of GRASE resulting from the use of additional gradient echoes is a potentially desirable attribute for use with SPIO enhancement.…”
Section: Discussionmentioning
confidence: 99%